ALTERNATIVE OPTICAL METHODS FOR QUALITATIVE DETECTION OF VITAMIN B6 AND B12 OF BANANA - Isnaeni Isnaeni; Baladika Sukma Zufara; Ismira Wahyu Lewa (Jurnal Teknologi dan Industri Pangan, 2020)
Bananas are known to contain fiber and vitamins essential for human body. Thus, the ability to detect these of vitamin in bananas is crucial. Information in the vitamin content of can affect procedures for harverst and post-harvest process. Methods to determine the nutrition content of foods are usually carried out using High Performance Liquid Chromatography (HPLC). However, this method requires complex sample preparation and chemical reaction processes. Due to this weakness, alternative techniques are needed to detect vitamin in simple ways. In this study, a simple, easy and fast methods to determine the vitamin content of banana was developed. Using reflectance and photoluminence spectroscopy, the vitamin of bananas from five different species were able to be identified. From the reflectance spectra results, two peaks were observed, the first peak at a wavelength of 325 nm is the absorption peak of vitamin B6 and the second peak at 450 nm is the absorption peak of vitamin B12. From the photoluminence spectra using excitation wavelength at 325 nm, an emission peak was found at wavelength 450 nm which is the peak emission from vitamin B6. These results proved that by using the methods proposed, the detection of vitamins in bananas can be done in an easy and simple ways.